Three presentations of CNS disease in patients with intraocular retinoblastoma at a tertiary medical center in the United States. (2nd January 2018) - Kim, Jonathan W; Jacobsen, Bradley H.; Ko, Marcus; Lee, Diana K; Jubran, Rima F; Berry, Jesse L
ABSTRACT: Background: Patients with intraocular retinoblastoma who present with central nervous (CNS) disease at diagnosis is very rare in developed countries. Methods: Herein, we report a review of patients with intraocular retinoblastoma diagnosed with concurrent CNS disease in the United States between January 2011 and June 2013. Results: Three patients were identified in this review. The first case is a 2-year old male who presented with unilateral Group E retinoblastoma, optic nerve infiltration to the orbital apex, and a suprasellar mass. The second case is a 5-month old female with bilateral retinoblastoma, who had no optic nerve invasion, but demonstrated a temporal lobe lesion that was biopsy-proven to be metastatic retinoblastoma. The third case is a 10-month old girl with bilateral retinoblastoma who presented with a sellar mass and no evidence of optic nerve invasion in the enucleated Group E eye. Conclusions: Although rare in developed countries, patients with intraocular retinoblastoma can present with a spectrum of CNS findings at the time of diagnosis. Magnetic resonance imaging of the brain and orbits is a critical component of the staging evaluation.